THE ROLE OF ULTRASOUND-GUIDED POPLITEAL NERVE BLOCK IN OPIOID-FREE ANESTHESIA FOR AN OSTEOSYNTHESIS MATERIAL EXTRACTION AFTER BILATERAL CALCANEAL FRACTURE - Chavkoska, Marina; Naumovski, Filip; Cvetkovа Mladenovska, Marija (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Peripheral nerve blocks (PNBs) for intraoperative and perioperative pain management are often part of the anesthetic plan for foot and ankle surgery. Usage of peripheral nerve blocks may limit occurrence of general anesthesia related complications by decreasing the amount of intraoperative anesthetic medications usage. Decreased postoperative opioids use and earlier time to discharge were encountered when peripheral nerve blocks were used. This case presentation is about a 38-year-old male patient with bilateral calcaneal OSM extraction and left calcaneal osteotomy, who refused spinal anesthesia, as well as refused to be awake during the procedure. Avoiding opioids was possible with usage of bilateral ultrasound-guided popliteal nerve block with 10 ml of 2% Lidocaine on each side. The purpose of this case report is to present the role of PNBs in intraoperative and postoperative decrease of opioids usage, as well as the absolute hemodynamic stability met during the procedure and pain-free extubated and awakened patient.
Keywords: Popliteal Nerve block; Opioid free anesthesia; Ultrasound guided nerve block